Young Adult Survey. Theoretical Foundation of an Indicator System for Cross Cur-ricular Competencies and Some Empirical Findings on its validation. - Grob, Urs; Merki, Katharina Maag; Büeler, Xaver (Swiss Journal of Educational Research, 2003)
This article describes the theoretical and methodological basis and presents some of the results of the pretests of the «Young Adult Survey (YAS)». This project is within the frame-work of the newly conceptualized «Eidgenössische Jugend- und Rekrutenbefragungen ch-x» which aims at the development of an indicator system for «cross curricular competencies» («überfachliche Kompetenzen») of young adults in Switzerland. Two empirical elements of the developmental work will be presented: First, the identification of relevant dimensions of «cross curricular competencies» by analyzing cantonal curricula, and second, information on the quality of the operationalisation. This will take place in the form of reliability indices of the psychometric scales and of an exploratory meta-factor-analysis. The results with regard to objectivity, reliability and validity suggest that the objectives of the development of the in-struments have adequately been met.